Low-power integration technology and energy efficiency optimization of chip packaging for AIoT underwater vehicles - Tang, Cheng; Chua, Antonette V. (Edelweiss Applied Science and Technology, 2026)
This paper focuses on low-power integration technology and energy efficiency optimization of chip packaging for AIoT underwater vehicles, conducting in-depth research on key technologies and proposing a set of low-power, high-reliability chip packaging integration schemes suitable for AIoT underwater vehicles. Firstly, through literature research and field investigation, it clarifies the research status of AIoT underwater vehicles and low-power chip packaging technology, and analyzes the special requirements of chip packaging for AIoT underwater vehicles. Secondly, it carries out research on key technologies such as low-power 3D stacked packaging structure based on TSV, integrated heat dissipation packaging technology, chiplet-based heterogeneous integration technology, and intelligent energy management strategy, establishing the corresponding mathematical models and design schemes. Thirdly, it designs and fabricates the prototype of the low-power chip packaging system and builds an experimental platform for performance testing. Fourthly, it conducts experiments to test the power consumption, heat dissipation performance, reliability, and system endurance of the prototype, optimizing the scheme according to the experimental results. Finally, it summarizes the research results, highlights the innovation points and application prospects, and forms the final research report. Additionally, this paper also designs an intelligent energy management strategy based on the working state of AIoT underwater vehicles.